2015
DOI: 10.1038/ncomms8906
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of insulin sensitivity in the mature adipocyte is sufficient for systemic metabolic improvements

Abstract: Dysfunctional adipose tissue represents a hallmark of type 2 diabetes and systemic insulin resistance, characterized by fibrotic deposition of collagens and increased immune cell infiltration within the depots. Here we generate an inducible model of loss of function of the protein phosphatase and tensin homolog (PTEN), a phosphatase critically involved in turning off the insulin signal transduction cascade, to assess the role of enhanced insulin signaling specifically in mature adipocytes. These mice gain more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 24 publications
1
77
0
1
Order By: Relevance
“…A tight regulation of insulin action in adipose tissue is required for the proper modulation of nutrient storage and mobilization throughout the daily cycles of fasting and feeding [7], [51], [52]. Our in vitro and in vivo results combined suggest that removal of GPS2-mediated regulation is sufficient to promote aberrant activation of the insulin signaling pathway through constitutive phosphorylation and activation of AKT.…”
Section: Resultsmentioning
confidence: 66%
“…A tight regulation of insulin action in adipose tissue is required for the proper modulation of nutrient storage and mobilization throughout the daily cycles of fasting and feeding [7], [51], [52]. Our in vitro and in vivo results combined suggest that removal of GPS2-mediated regulation is sufficient to promote aberrant activation of the insulin signaling pathway through constitutive phosphorylation and activation of AKT.…”
Section: Resultsmentioning
confidence: 66%
“…Among them, phosphatase and tensin homolog deleted on chromosome 10 (PTEN) antagonizes PI3K actions to negatively regulate the phosphorylation of AKT. Numerous studies revealed that overexpression of PTEN could suppress insulin-induced PtdIns (3,4) P2/PtdIns (3,4,5) P3 PIP3 production, thereby inhibiting AKT activation, GLUT4 translocation and glucose uptake121314.…”
mentioning
confidence: 99%
“…The importance of coordinated adipose tissue expansion in the maintenance of whole body metabolic homeostasis is well-established (Acosta et al 2016, Henninger et al 2014, Morley et al 2015 and increasing evidence provides a link between the FGF-1 axis and obesity-related adipose tissue remodeling (Jonker et al 2012, Ohta andItoh 2014). Hence, we sought to extend our in vitro observations by exploring the relationship between expression of CPA4 in shAT with indices of adipose tissue and hepatic and muscle insulin sensitivity in a cohort of obese males who had been subject to comprehensive metabolic characterization (Chen et al 2015).…”
mentioning
confidence: 99%